The remote area nurse model of consultation - Lenthall, Sue; Knight, Sabina; Foxley, Sally; Gordon, Vicki; Ivanhoe, Terrie; Aitken, Robyn (International Journal of Advanced Nursing Studies, 2015)
Registered nurses working in remote areas of Australia are often called remote area nurses (RANs). RANs have traditionally used models of client consultation designed for acute presentations and episodes of care. However, presentations to health care facilities in remote Australia are more likely to be chronic, complex, multi-system and multifactorial in origin and subsequent management. This paper describes a consultation model developed from a combination of expert opinion, literature and trial and feedback from RANs. The model is comprehensive, systematic and puts the person at the centre of care. It aims to mitigate risk for the client; the RAN and the health service while at the same time building trust and health literacy between the client and the RAN to encourage the client to continue with the partnership in care.